The effects of time of day-specific resistance training on adaptations in skeletal muscle hypertrophy and muscle strength: A systematic review and meta-analysis - Grgic, J.; Lazinica, B.; Garofolini, A.; Schoenfeld, B. J.; Saner, N. J.; Mikulic, P. (Chronobiology International, 2019)
The present paper endeavored to elucidate the topic on the effects of morning versus evening resistance training on muscle strength and hypertrophy by conducting a systematic review and a meta-analysis of studies that examined time of day-specific resistance training. This systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines with searches conducted through PubMed/MEDLINE, Scopus, and SPORTDiscus databases. The Downs and Black checklist was used for the assessment of the methodological quality of the included studies. Studies that examined the effects of time of day-specific resistance training (while equating all other training variables, such as training frequency and volume, between the groups) on muscle strength and/or muscle size were included in the present review. The random effects model was used for the meta-analysis. Meta-analyses explored the differences in strength expression between morning and evening hours at baseline; the differences in strength within the groups training in the morning and evening by using their post-intervention strength data from the morning and evening strength assessments; the overall differences between the effects of morning and evening resistance training (with subgroup analyses conducted for studies that assessed strength in the morning hours and for the studies that assessed strength in the evening hours). Finally, a meta-analysis was also conducted for studies that assessed muscle hypertrophy. Eleven studies of moderate and good methodological quality were included in the present review. The primary findings of the review are as follows: at baseline, a significant difference in strength between morning and evening is evident, with greater strength observed in the evening hours; resistance training in the morning hours may increase strength assessed in the morning to similar levels as strength assessed in the evening; training in the evening hours, however, maintains the general difference in strength across the day, with greater strength observed in the evening hours; when comparing the effects between the groups training in the morning versus in the evening hours, increases in strength are similar in both groups, regardless of the time of day at which strength assessment is conducted; and increases in muscle size are similar irrespective of the time of day at which the training is performed. Abstract from author